Barriers of providing transitional services for adolescent students with autism spectrum disorder: Saudi teachers’ perspective - Almutlaq, Hajar; Almutairi, Badriah (Edelweiss Applied Science and Technology, 2025)
Transitional services play a crucial role in helping individuals identify personal goals, develop skills, and connect with community resources, thereby enhancing their quality of life, reducing isolation, and increasing opportunities for employment and social engagement, particularly for individuals with disabilities. Previous research has highlighted a gap in the implementation of transitional services within educational settings. This study aims to identify the barriers to transitional services for adolescent students with autism and explore strategies to improve their effectiveness. A descriptive survey methodology was used, with data collected through a questionnaire administered to a random sample of 144 teachers of adolescent students with autism spectrum disorder in public schools under the Ministry of Education in Riyadh. The findings revealed that although teachers recognize the significance of transitional services for these students, there is a lack of knowledge regarding essential transitional services. Furthermore, there are deficiencies in the preparation and professional development programs for teachers related to these services. The study suggests the introduction of targeted programs to improve teachers’ understanding of transitional services for students with autism spectrum disorder, as well as providing training to enhance their ability to deliver and evaluate these services effectively.